Analisis Studi Literatur Pengaruh Teknik dan Sudut Pemangkasan Terhadap Hasil Akhir Pemangkasan Rambut - Maghfiroh, Anik; Nurhayati, Ifa; Alfatia, Ainaya; Ayu, Niken; Putri, Dinda; Kesya, Salsa (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Basic techniques in hair cutting are basic skills that must be mastered as a foundation in learning various types of cuts. This study aims to examine the effect of cutting techniques and angles on the final results of haircuts through a literature study approach. The method used involves searching for various relevant theoretical sources, such as scientific journals, books, and related articles. The results of the analysis show that cutting techniques (such as blunt cut, point cut, slide cut, and razor cut) and variations in cutting angles (starting from 0°, 45°, 90°, to 180°) have a major effect on the texture, volume, and final shape of the hair. Choosing the right combination of techniques and angles can produce a haircut that is in harmony with the shape of the face, increases aesthetic value, and meets the client's desires. These findings are an important reference for hairdressers in determining precise and aesthetic cutting methods.